Effect of bagasse as a roughage source on nutrient digestibilty and growth performance of growing crossbred dairy calves: Effect of bagasse as a roughage source on nutrient digestibilty and growth. dairy calves - Rajkumar, K; Meenakshi Sundaram, S; Manobhavan, M; Muthuramalingam, T; Chaidanya, K; Sivarani, J (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was undertaken with an objective to evaluate the effect of sugarcane bagasse as analternate roughage source on the feed intake, nutrient digestibility and growth performance in crossbred calves. Eighteen crossbred calves aged one year with an average body weight of154.28 kg were utilised in the study for 6 months. The animals were divided into 3 groups and fed with two different inclusion levels of sugarcane bagasse (25% and 50%) replacing conventional fodder and a control diet based on roughage and concentrates, commonly adopted in the region. There was no significant (p>0.05) difference between control and treatment groups in the digestibility of DM, OM, CF, NFE, however the digestibility of EE differed significantly (p<0.05).Even though DCP showed highly significant difference among the groups, the TDN contents were similar to the control diets for both treatment groups. The dry matter intake did not differ significantly for the 1st and 2nd months. There was no significant (p>0.05) difference in the bodyweight of the animals in the entire study period.Therefore sugarcane bagasse can be safely included up to the level of 50% in the diet and can potentially replace the conventional green fodder without affecting the growth and daily dry matter intake in crossbred growing calves.